Economic Burden of Major Diseases in China in 2013 - Song, Xianyan; Lan, Lan; Zhou, Ting; Yin, Jin; Meng, Qiong (Frontiers in Public Health, 2021)
Studies on the economic burden of disease (EBD) can estimate the social benefits of preventing or curing disease. The majority of studies focus on the economic burden of a single or regional disease; however, holistic or national research is rare in China. Estimating the national EBD can provide evidence for policy makers. We used the top-down method to assess the economic burden of 30 types of diseases between urban and rural areas in China. The two-step model was used to evaluate the direct economic burden of disease (DEBD), while the human capital method was used to assess the indirect economic burden of disease (IEBD). The total economic burden of 30 types of diseases in China was between 13.39 and 803.00 billion in 2013. The average total economic burden of disease (TEBD) in cities was 81.39 billion, while diseases in villages accounted for 50.26 billion. The range of direct and indirect EBD was 5.77-494.52 billion, and the range in urban areas was 0.61-20.34 billion. The direct and indirect EBD in rural areas accounted for 5.88 to 277.76 billion and 0.59 to 11.39 billion, respectively. There was a large difference between the economic burden of different diseases. The economic burden of urban diseases was more significant than the burden for the rural. The top five most economically burdensome diseases were myocardial infarction coronary artery bypass, acute myocardial infarction, cerebral hemorrhage, acute upper gastrointestinal bleeding and acute appendicitis.